2020
DOI: 10.2478/jtim-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: Harnessing iPSC-derived cells for ischemic heart disease treatment

Abstract: Ischemic heart disease (IHD) is one of the most common cardiovascular diseases and is the leading cause of death worldwide. Stem cell therapy is a promising strategy to promote cardiac regeneration and myocardial function recovery. Recently, the generation of human induced pluripotent cells (hiPSCs) and their differentiation into cardiomyocytes and vascular cells offer an unprecedented opportunity for the IHD treatment. This review briefly summarizes hiPSCs and their differentiation, and presents the recent ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The ability to develop patient-derived hiPSCs have opened new avenues to tailor personalized medicine approaches for numerous disorders and degenerative diseases [ 2 ]. Furthermore, the expandability and pluripotency of hiPSCs has been critical for their use in developing cell-based therapies for traumatic brain injury [ 3 , 4 ], spinal cord injury [ 5 , 6 ], myocardial infarction [ 7 , 8 ], acute kidney injury [ 9 ], and diabetes mellitus [ 10 , 11 ]. However, despite the improved functional outcomes observed in preclinical studies involving hiPSC-based cell therapy, several studies reported poor engraftment and long-term survival of the transplanted cells [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to develop patient-derived hiPSCs have opened new avenues to tailor personalized medicine approaches for numerous disorders and degenerative diseases [ 2 ]. Furthermore, the expandability and pluripotency of hiPSCs has been critical for their use in developing cell-based therapies for traumatic brain injury [ 3 , 4 ], spinal cord injury [ 5 , 6 ], myocardial infarction [ 7 , 8 ], acute kidney injury [ 9 ], and diabetes mellitus [ 10 , 11 ]. However, despite the improved functional outcomes observed in preclinical studies involving hiPSC-based cell therapy, several studies reported poor engraftment and long-term survival of the transplanted cells [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glutaminase 2 (GLS2) can cause ROS accumulation through mitochondria by accelerating glutamate formation ( Matés et al, 2020 ). After myocardial infarction, cardiomyocytes often undergo cell death and pathological remodeling, which easily lead to heart failure ( Duan, 2020 ). Zhou et al have suggested that miR-190a-5p inhibits cardiomyocyte ferroptosis by inhibiting GLS2 and decreases the levels of ROS, MDA, and Fe 2+ in H9c2 cells, thus playing a protective role in myocardial infarction ( Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the complex pathologic process of MIRI, various stages are involved, involving platelet activation, oxidative stress, endothelial dysfunction, and inflammatory response (5). Therapeutic strategies for MIRI mainly consist of non-pharmacological interventions (ischemic preconditioning, ischemic postconditioning, and remote ischemic preconditioning), pharmacological interventions (cyclosporine A, atrial natriuretic peptide, and glucagonlike peptide 1) (6,7), and even implementation of humaninduced pluripotent cells (8). Although cell and animal experiments have confirmed the effectiveness of the therapies, the results of clinical trials have been disappointing.…”
Section: Introductionmentioning
confidence: 99%